2014
DOI: 10.4040/jkan.2014.44.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Korean Version of the Pain Assessment Checklist for Seniors with Limited Ability to Communicate

Abstract: Purpose: This study was done to develop and test the validity and reliability of the Korean version of the Pain Assessment Checklist for Seniors with Limited Ability to Communicate (PACSLAC-K) in assessing pain of elders with dementia living in long-term care facilities. Methods: The PACSLAC-K was developed through forward-backward translation techniques. Survey data were collected from 307 elders with dementia living in 5 long-term care facilities in Korea. Data were analyzed using descriptive statistics, Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…These scales contain all or some of the six behavioral indices recommended by the GSA, and include the Pain Assessment Checklist for Seniors with Limited Ability to Communicate (PAC-SLAC) ( Fuchs-Lacelle & Hadjistavropoulos, 2004 ), Discomfort Scale-Dementia of the Alzheimer Type (DS-DAT) ( Hurley et al, 1992 ), Doloplus-2 ( Rostad et al, 2017 ), Pain Assessment in Advanced Dementia (PAINAD) ( Warden et al, 2003 ), Checklist of Nonverbal Pain Indicators (CNPI) ( Feldt, 20 0 0 ), and Pain Assessment for Demented Elderly (PADE) ( Villanueva et al, 2003 ). Among these scales, only the PACSLAC has been validated in Korea ( Kim et al, 2014 ); it encompasses all six behavioral indices suggested by the GSA and can thus detect even small behavioral changes. However, as the PAC-SLAC is a lengthy instrument consisting of 60 items, which may be useful for monthly or quarterly assessments but is not appropriate for clinical practitioners in Korea that must assess patients' pain several times a day to provide immediate interventions ( Lee & Song, 2016 ).…”
Section: Article In Pressmentioning
confidence: 99%
“…These scales contain all or some of the six behavioral indices recommended by the GSA, and include the Pain Assessment Checklist for Seniors with Limited Ability to Communicate (PAC-SLAC) ( Fuchs-Lacelle & Hadjistavropoulos, 2004 ), Discomfort Scale-Dementia of the Alzheimer Type (DS-DAT) ( Hurley et al, 1992 ), Doloplus-2 ( Rostad et al, 2017 ), Pain Assessment in Advanced Dementia (PAINAD) ( Warden et al, 2003 ), Checklist of Nonverbal Pain Indicators (CNPI) ( Feldt, 20 0 0 ), and Pain Assessment for Demented Elderly (PADE) ( Villanueva et al, 2003 ). Among these scales, only the PACSLAC has been validated in Korea ( Kim et al, 2014 ); it encompasses all six behavioral indices suggested by the GSA and can thus detect even small behavioral changes. However, as the PAC-SLAC is a lengthy instrument consisting of 60 items, which may be useful for monthly or quarterly assessments but is not appropriate for clinical practitioners in Korea that must assess patients' pain several times a day to provide immediate interventions ( Lee & Song, 2016 ).…”
Section: Article In Pressmentioning
confidence: 99%
“…Previous studies showed that PACSLAC has sufficient internal consistency scores reliability (6,15,28,33,34). In the original PACSLAC study, the Cronbach's α value was 0.92, while in other published versions of the scale it was shown to vary between 0.827 and 0.917.…”
Section: Discussionmentioning
confidence: 96%
“…Among the types of dementia, Alzheimer’s was the most prevalent, in 59.2% of participants; this is consistent with the literature that reports the condition as the most common cause of dementia. ( 34 ) The most frequent answer for probable causes of pain was muscle and joint pain (89.8% and 85.7%, respectively). These data are supported by the literature, which describe bone diseases are conditions that are highly associated with pain by demented elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…These data are supported by the literature, which describe bone diseases are conditions that are highly associated with pain by demented elderly patients. ( 34 )…”
Section: Discussionmentioning
confidence: 99%